1996
DOI: 10.1128/aem.62.10.3581-3586.1996
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic activity of a Bacillus thuringiensis delta-endotoxin and a bacterial endochitinase against Spodoptera littoralis larvae

Abstract: In an attempt to increase the insecticidal effect of the ␦-endotoxin crystal protein CryIC on the relatively Cry-insensitive larvae of Spodoptera littoralis, a combination of CryIC and endochitinase was used. CryIC comprising the first 756 amino acids from Bacillus thuringiensis K26-21 and endochitinase ChiAII encoded by Serratia marcescens were separately produced in Escherichia coli carrying the genes in overexpression vectors. The endochitinase on its own, even at very low concentrations (0.1 g/ml), perfora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(84 citation statements)
references
References 54 publications
4
73
0
2
Order By: Relevance
“…Interestingly, the chitinase-producing B. thuringiensis or its related species B. cereus strains can enhance the insecticidal toxicity of active B. thuringiensis strains (Morris 1976;Sneh et al 1983). This finding might be applied for the development of new B. thuringiensis formulations (Tabashnik 1992;Regev et al 1996;Sampson and Gooday 1998;Wiwat et al 2000). Several reports have described selection and characterization of chitinolytic B. thuringiensis strains (Barboza-Corona et al 1999;Rojas-Avelizapa et al 1999).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Interestingly, the chitinase-producing B. thuringiensis or its related species B. cereus strains can enhance the insecticidal toxicity of active B. thuringiensis strains (Morris 1976;Sneh et al 1983). This finding might be applied for the development of new B. thuringiensis formulations (Tabashnik 1992;Regev et al 1996;Sampson and Gooday 1998;Wiwat et al 2000). Several reports have described selection and characterization of chitinolytic B. thuringiensis strains (Barboza-Corona et al 1999;Rojas-Avelizapa et al 1999).…”
Section: Introductionmentioning
confidence: 85%
“…Subsequently destruction of the transmembrane potential and the osmotic lysis of cells lining the midgut cause the death of the larvae (Gill et al 1992;Aronson and Shai 2001). Some reports revealed that chitinase could enhance this process and might be used to improve the pesticidal activity of B. thuringiensis (Regev et al 1996;Sampson and Gooday 1998;Wiwat et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It is long since known that chitinase activities resulting in the degradation of the PM play key roles in the virulence of entomopathogens that are transmitted orally and infect insects via the midgut that is normally shielded by the PM. One known mechanism is that toxins can more easily act on the epithelial cells if they are no longer protected by the PM (Sneh et al, 1983;Regev et al, 1996;Sampson and Gooday, 1998;Ramirez-Suero et al, 2011;Bahar et al, 2012). We recently found genetic evidence for the presence of toxin genes in the genome of P. larvae (Fünfhaus et al, 2009).…”
Section: Paenibacillus Larvae Degrades the Pm In Infected Larvaementioning
confidence: 99%
“…This perforation may provide an access for TMOF to be delivered into the gut cells and initiates its sequential effects. Previous results obtained by Regev et al (1996) indicated that pore formation of the peritrophic matrix, caused by chitinase, enhanced the CryIC toxicity towards S. littoralis.…”
Section: Discussionmentioning
confidence: 87%